Ecotoxicology of manufactured graphene oxide nanomaterials and derivation of preliminary guideline values for freshwater environments. (26th February 2018) - Markovic, Marijana; Kumar, Anupama; Andjelkovic, Ivan; Lath, Supriya; Kirby, Jason K.; Losic, Dusan; Batley, Graeme E.; McLaughlin, Michael J.
Abstract: The unique physical and chemical properties of graphene‐based nanomaterials (GNMs) have inspired a diverse range of scientific and industrial applications. The market value of GNMs is predicted to reach $US 1.3 billion by 2023. Common to many nanomaterials, an important and unresolved question is the environmental consequences of the increases in GNMs use. The current deficiencies in studies reporting ecotoxicology data for GNMs include differences in analytical methodologies for quantification, no standardized test guidelines, differences in morphology of GNMs, the lack of Chemical Abstract Service numbers, and the quality of the reported data. The assessment of potential adverse effects on aquatic organisms typically relies on guideline values based on species sensitivity distributions (SSDs) of toxicity data. We present preliminary water quality guideline values for graphene oxide NMs in freshwaters. Data include 10 species from 7 phyla (bacteria and fungi were not included). The most sensitive organism was found to be the freshwater shrimp Palaemon pandaliformis . The derived guideline values for 99, 95, 90, and 80% species protection were 350, 600, 830, and 1300 μg/L, respectively. These results will contribute to the regulatory derivations of future water quality guideline values for graphene‐based NMs. Environ Toxicol Chem 2018;37:1340–1348. © 2018 SETAC